2017
DOI: 10.1039/c6ra28149d
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of telomerase capping by short non-toxic peptides via arresting telomeric G-quadruplex

Abstract: The stabilization of a G-quadruplex structure in human telomeric DNA has become a promising strategy in the development of cancer therapeutics. Here, we report FK13 (a small fragment of human cathelicidin peptide LL37, residues 17-29) and its mutant peptides (KR12A, KR12B and KR12C) inhibiting telomerase activity by stabilizing the telomeric G-quadruplex structures. An array of biophysical studies like fluorescence anisotropy, circular dichroism spectroscopy, circular dichroism melting, isothermal titration ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…A high specificity towards G4 against double-strand DNA has also been observed. [69] NMR spectroscopy has highlighted the interaction of the R7, R3, and R13 with the phosphate backbone of the G4, while MD simulations, coherently with the previous observation on the entire LL37 peptide, have proven that FK13 loses its helicity while interacting with the G4. On the other hand, FK13 treatment on MCF7 breast cancer cells leads to a significative inhibition of their growth, in a dose-dependent manner.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...supporting
confidence: 72%
See 2 more Smart Citations
“…A high specificity towards G4 against double-strand DNA has also been observed. [69] NMR spectroscopy has highlighted the interaction of the R7, R3, and R13 with the phosphate backbone of the G4, while MD simulations, coherently with the previous observation on the entire LL37 peptide, have proven that FK13 loses its helicity while interacting with the G4. On the other hand, FK13 treatment on MCF7 breast cancer cells leads to a significative inhibition of their growth, in a dose-dependent manner.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...supporting
confidence: 72%
“…Indeed, FK13 (FKRIVQRIKDFLR) has been shown to bind to h‐Telo G4, and thus provide additional structural stability. A high specificity towards G4 against double‐strand DNA has also been observed [69] . NMR spectroscopy has highlighted the interaction of the R7, R3, and R13 with the phosphate backbone of the G4, while MD simulations, coherently with the previous observation on the entire LL37 peptide, have proven that FK13 loses its helicity while interacting with the G4.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…So far, we observed that KR12C is the best peptide candidate that selectively repressed c-MYC promoter activation in cancer cells. Earlier reports showed its ability to trigger apoptosis in cancer MCF-7 cells ( 89 ). We further validated these results through monitoring the expression profiles of different oncogenes and apoptosis markers in order to deduce the mechanism how G-quadruplex stabilization at c-MYC promoter triggered selective apoptosis in cancer cells.…”
Section: Resultsmentioning
confidence: 98%
“…Smits et al. showed that the decreased expression of miR-125b by VEGF results in an upregulation of MAZ (Myc-associated zinc finger protein) expression, which specifically binds to a GA box sequence (GGGAGGG) in c-MYC- P 2 promoter to regulate c-MYC transcription ( 88 , 89 ). Since FK13 and KR12B strongly inhibited VEGF-A promoter activity and its transcription, the negative effects of these peptides on c-MYC promoter might be due to their non-specific targeting at VEGF-A quadruplexes.…”
Section: Resultsmentioning
confidence: 99%